Fundamental Determinants of the Effects of Fiscal Policy - Kumar, Manmohan; Botman, Dennis (Washington, D.C. : International Monetary Fund, 2006)
We explore the underlying determinants of the macroeconomic effects of fiscal policy and tax and social security reform using the Global Fiscal Model (GFM). We show that the planning horizon of consumers, access to financial markets, and the elasticity of labor supply, as well as the characteristics of utility and production functions, and the degree of competition are all critical for determining the impact of fiscal policy. Four topical fiscal policy issues, for a representative large and small economy, are examined: the effects of changes in government debt; higher government spending; tax reform; and privatization of retirement savings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet